Variable response of eastern filbert blight resistance sources in New Jersey - Jacobs, Daniel C.; Revord, Ronald S.; Capik, John M.; Mehlenbacher, Shawn A.; Molnar, Thomas J. (Frontiers in Plant Science, 2024)
Eastern filbert blight (EFB), caused by Anisogramma anomala, is the primary limiting factor for hazelnut (Corylus sp.) production in the United States. In this study, 82 cultivars and selections shown to be resistant or tolerant to EFB in Oregon were field planted in New Jersey in 2017 and 2019 and evaluated for their EFB response under high disease pressure. The trees carry known single resistance (R) genes with most mapped to their respective linkage groups (LG), including LG2, LG6, and LG7, or they express quantitative resistance (QR, horizontal resistance). Disease incidence and severity was documented, stem cankers counted and measured, and the proportion of diseased wood calculated. The EFB disease response of some cultivars/selections varied considerably between New Jersey and Oregon while others were consistent. Trends were observed in relation to resistance source origin and LGs, which provide insight into durability and usefulness of resistance. In striking contrast to Oregon, nearly all selections with R-genes mapped to LG6, including those carrying the 'Gasaway' resistance allele, exhibited severe EFB infections (232 of 266 [87%]). This finding is of consequence since the U.S. hazelnut industry currently relies solely on LG6 resistance for EFB resistance. Further, for the first time, EFB was observed on several selections carrying LG7 resistance, specifically offspring of 'Ratoli' from Spain. Interestingly, selections carrying LG7 resistance from origins other than 'Ratoli' remained free of EFB, with one exception, all selections carrying LG2 (n=9) resistance also remained free from EFB. Interestingly, the EFB responses of selections expressing QR (n=26) more closely resembled the disease phenotypes they exhibited in Oregon. Overall, the divergence in EFB response between Oregon and New Jersey, where pathogen populations differ, supports the presence of pathogenic variation in A. anomala and highlights potential limitations of using single R-genes to manage the disease. Results also suggest trees expressing QR may be more stable across pathogenic populations.